Investment motivation, investment knowledge, investment risk perception on investment decisions mediated by investment interest - Sarumaha, Dekapoli; Sugiyanto, Liem Bambang (International Journal Labs, 2023)
This research aims to identify the relationship between the variables observed in this group of subjects. The main data source was obtained by collecting data from respondents using questionnaires online or in person when meeting students at Bunda Mulia University on the Ancol campus and Serpong campus, and subordinate data sources were obtained from the literature study. The results of processing respondent data found that the investment motivation variable has a negative and significant effect on students' investment decisions in the capital market. The second hypothesis is that investment knowledge is a factor that influences investment decisions in the Theory of Planned Behavior (TPB). It can be interpreted that investment interest acts as a mediating factor that bridges the relationships between the independent variables and dependent variables. Therefore, it is hoped that students will be able to provide education about investment to the public as well as advance the Indonesian capital market, especially for students at Jenderal Soedirman University, so that the number of new investors among students continues to increase and increase.